2013
DOI: 10.1109/jsac.2013.130320
|View full text |Cite
|
Sign up to set email alerts
|

Service Response Time of Elastic Data Traffic in Cognitive Radio Networks

Abstract: Abstract-Quality of service (QoS) support over cognitive radio networks (CRNs) is challenging due to the random spectrum availability. Elastic data traffic is a popular service whose service response time is an important QoS parameter. We analyze the mean response time of elastic data traffic service operating over a single channel time-slotted centralized CRN under three main service disciplines, namely, shortest processing time without preemption (SPTNP), shortest processing time with preemption, and shortes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 21 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Tran et al [20] evaluate the average service time of delay-sensitive and delay-insensitive packets showing that the average service time of the packets transmitted by a SU not only depends on the arrival rate and size of SU's packets but also on the arrival rate and size of the PU's packets. In [21] the service time is analyzed for a single channel CRN and the analysis is extended in [22] to characterize the average service response time of elastic data (i.e., variable packet-length) when the PU activity follows an ON-OFF behavior with ON and OFF durations following exponential distributions. While the previous works only characterize the average of the service time, [23] derived expressions for the distribution of the packet service time when the SUs are traffic-saturated and fixed-length packets are transmitted.…”
Section: A Related Workmentioning
confidence: 99%
“…Tran et al [20] evaluate the average service time of delay-sensitive and delay-insensitive packets showing that the average service time of the packets transmitted by a SU not only depends on the arrival rate and size of SU's packets but also on the arrival rate and size of the PU's packets. In [21] the service time is analyzed for a single channel CRN and the analysis is extended in [22] to characterize the average service response time of elastic data (i.e., variable packet-length) when the PU activity follows an ON-OFF behavior with ON and OFF durations following exponential distributions. While the previous works only characterize the average of the service time, [23] derived expressions for the distribution of the packet service time when the SUs are traffic-saturated and fixed-length packets are transmitted.…”
Section: A Related Workmentioning
confidence: 99%
“…For details see [2]. The vast majority of the models developed for studying CR networks, and specifically for spectrum sensing, assume that busy and idle times follow an exponential distribution (or geometric in discrete time); for example, see [14,15] and all the above references to sensing studies. Using measurements, the authors of [16] showed that the channel idle time can be modeled by a lognormal distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of models that have been developed for studying CR networks, and in particular for studying spectrum sensing, assume that the durations of both the busy and idle times are governed by the exponential distribution (or its discrete time counterpart: geometric), see for example [18,19] and all the references given above for sensing related studies. However, this assumption is not backed with empirical evidence.…”
Section: Introductionmentioning
confidence: 99%